2019
DOI: 10.1083/jcb.201904051
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced senescent cancer cells engulf other cells to enhance their survival

Abstract: In chemotherapy-treated breast cancer, wild-type p53 preferentially induces senescence over apoptosis, resulting in a persisting cell population constituting residual disease that drives relapse and poor patient survival via the senescence-associated secretory phenotype. Understanding the properties of tumor cells that allow survival after chemotherapy treatment is paramount. Using time-lapse and confocal microscopy to observe interactions of cells in treated tumors, we show here that chemotherapy-induced sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 55 publications
(111 reference statements)
5
110
0
Order By: Relevance
“…The cells that escaped senescence exhibited more invasive and migratory properties. In fact, it has recently been reported that doxorubicin-induced senescent breast tumor cells develop a cannibalistic capacity that allows for the engulfment of adjacent senescent and non-senescent neighbors [164]. This acquisition of a phagocytic capability enables senescent cells to hijack nutrient cargos from other cells, which can then be utilized to prolong their survival, providing an additional explanation for how senescent tumor cells can persist following exposure to anticancer therapy [165].…”
Section: Evidence For the Reversibility Of Therapy-induced Senescencementioning
confidence: 99%
“…The cells that escaped senescence exhibited more invasive and migratory properties. In fact, it has recently been reported that doxorubicin-induced senescent breast tumor cells develop a cannibalistic capacity that allows for the engulfment of adjacent senescent and non-senescent neighbors [164]. This acquisition of a phagocytic capability enables senescent cells to hijack nutrient cargos from other cells, which can then be utilized to prolong their survival, providing an additional explanation for how senescent tumor cells can persist following exposure to anticancer therapy [165].…”
Section: Evidence For the Reversibility Of Therapy-induced Senescencementioning
confidence: 99%
“…However, these cells can promote tumour survival by secreting growth factors and signalling molecules called cytokines in a process termed the senescence-associated secretory phenotype (SASP) response 2 . Tonnessen-Murray et al 4 report studies of breast cancer in mice which reveal that this type of senescent cell takes up (engulfs) and digests neighbouring living cells. The cells are engulfed by a process that has molecular characteristics of phagocytosis, an engulfment process that immune cells use.…”
Section: Michael Overholtzermentioning
confidence: 99%
“…Ancient air trapped in Antarctic ice can be extracted from cores drilled from the ice sheet, allowing the CO 2 concentration to be measured directly, but the ice-core record extends to only 800,000 years ago 4 . Estimates of CO 2 concentrations from earlier periods have been made by measuring the ratio of boron isotopes in shells found in ancient marine sediments 5,6 .…”
Section: Fresh Evidence In the Glacial-cycle Debate Eric W Wolffmentioning
confidence: 99%
See 1 more Smart Citation
“…To dissect the molecular mechanisms underlying the observed phenotype, Tonnessen-Murray et al (8) performed an RNA-sequencing analysis in doxorubicin-treated cancer cells collected at two different time points: before (24 h) and after the CISC-related cell engulfment reaches its peak (8 d). Intriguingly, with respect to untreated cells, the gene set enrichment analysis unveiled the induction of several pathways, including cell cycle arrest, lysosomal signature, and phagocytosis, thus suggesting that cells surviving doxorubicin treatment activate a macrophage-like transcriptional program that allows CISCs to surround neighboring cells, engulf them, and digest them via the lysosomes.…”
mentioning
confidence: 99%